Penerepan PETRUK dalam Kegiatan Ekstrakurikuler Berbasis Budaya sebagai Upaya Internalisasi Nilai-Nilai Kearifan Lokal - Yeni Agus Tri Puryanti; Marzuki Marzuki (Mudra Jurnal Seni Budaya, 2020)
The research objectives are to describe:(1)The application of "PETRUK" in culture-based extracurricular activities as an effort to internalize the values ​​of local wisdom.(2)Supporting factors for the application of "PETRUK" in culture-based extracurricular activities as an effort to internalize the values ​​of local wisdom.(3)Factors inhibiting the application of "PETRUK" in culture-based extracurricular activities as an effort to internalize the values ​​of local wisdom. The research approach uses qualitative with descriptive type. This research was conducted at SMP Negeri 3 Banguntapan Bantul. Determination of research subjects is done by purposive method. Data collection is done by field observations, in-depth interviews, and documentation. Test the validity of the data using triangulation techniques, then data analysis using the interactive data analysis model of Miles, Huberman and Saldana. The results of research at SMP Negeri 3 Banguntapan Bantul show (1)Internalization of local wisdom values ​​using the application of "PETRUK" (a)the letter P means modeling, (b)the letter E means empowering, (c)the letter T means teaching, (d)the letter R means reinforcing,(e)the letter U means unique, (f)the letter K means comprehensive. The values ​​of local wisdom internalized in karawitan extracurricular activities are 15 values, batik 10 values, dance 12 values ​​which are guided by DIY PERGUB No. 68 of 2012. (2)Among the inhibiting factors are students' lack of awareness in joining extracurricular activities and students accustomed to modern culture. (3) Supporting factors include, getting support from parents, government and society.